PERANCANGAN MEKANISME PENGGERAK PADA MESIN PEMBILAH BAMBU - Santo Ajie Dhewanto (Teknoin, 2016)
Bamboo is widely used as a product application material. More and more enthusiasts of products produced with bamboo laminate materials require special equipment with good performance for production. The existing bamboo laminate production equipment still requires much innovation for that purpose, which required improvement and addition of mechanism to improve its performance. The addition of a motion mechanism to the bamboo splitting tool improved the tool performance by 54%, and decrease in rolling time for bamboo from 23 seconds to 0.85 seconds. Increased performance of bamboo splitter will have a positive impact on production costs for small and medium enterprises, thereby increasing profits and increasing the competitiveness of products.